Xenotransplante ovariano de gatas domésticas em camundongas C57BL/6 SCID e sua resposta á gonadotrofina coriõnica equina - Santos, Fernanda Araujo dos (Universidade Federal Rural do Semi-Árido, 2015)
Ovarian xenografting is an auxiliary reproductive technique that allows the conservation of germplasm of high value livestock or endangered species. The use of exogenous gonadotropins assists in developing these xenografted tissues and obtaining viable follicles for in vitro embryo production (IVEP), however this use has not been reported in xenograftings of cats ovaries with C57BL/6 SCID female mice as recipients. Thus, the aim of this study was to evaluate the response of xenografting of domestic cat ovaries to equine chorionic gonadotropin (eCG) when grafted into C57BL/6 SCID female mice. Therefore, domestic cats ovarian cortex fragments were grafted under the kidney capsule of fifteen C57BL/6 SCID mice after bilateral ovariectomy. At the end of 45 days, the female mice were divided into two groups and those who did not receive hormone induction (eCG ) were euthanized at the time of induction. Females who received hormonal induction (eCG +) were euthanized after 48 hours. All collected tissues were taken for histologic processing. The proportions between the different ovarian follicles were compared by the chi-square test. The morphometric analysis of the follicles were compared between the experimental groups by the Tukey test (primordial follicles, primary and secondary) and Kruskal-Wallis (antral follicles). Macroscopically, it was possible to observe a low number (16%) of antral follicles with more than 1mm in transplants treated with eCG. In the microscopic analysis, follicles from all categories were observed in transplants and all had normal morphology and morphometry for the studied species (Felis catus), being however observed larger primordial and primary follicles in those eCG + transplants. There was a decrease in primordial follicles percentages and an increase in subsequent categories, mainly in antral follicles of eCG + group, and this condition is proposed here characterized as Follicular Right Shift (FRS). Luteinized follicles were also observed in transplants treated with eCG. Thus, it is concluded that the treatment with eCG is effective when it comes to follicular development, but it did not show a good superovulatory response
Xenografting of queens ovarian tissue into C57BL/6 female scid mice and its responses to equine chorionic gonadotropin
Keywords: Rodent; Female mice; Domestic cat; Xenografting ovary; Hormonal induction - eCG; Roedor; Camundonga; Gata doméstica; Xenotransplante ovariano; Indução hormonal - eCG; CIENCIAS AGRARIAS::MEDICINA VETERINARIA